Long-Term Radiologic Evaluation of Microaspirations among Patients after Esophagectomy - Pines, Guy; Jacobson, Francine; Zheng, Yifan; Magali, Pham; Lerut, Toni; Bueno, Raphael (The Thoracic and Cardiovascular Surgeon, 2020)
Objectives Aspirations are common after esophagectomy. Data are lacking regarding its long-term radiological manifestations. The purpose of this study is to determine the incidence and radiological patterns of aspirations among long-term survivors and evaluate their clinical significance.Methods The records of all patients who underwent esophagectomy between October 2003 and December 2011 and survived more than 3 years were reviewed. Preoperative, first routine postoperative, and latest chest computed tomography (CT)scans were reviewed. Imaging studies were reviewed for radiological signs suspicious of aspirations, conduit location, anastomotic site, and maximal intrathoracic diameter. Data regarding patients' complaints during clinic visits were also collected.Results A total of 578 patients underwent esophagectomy during the study period. One-hundred twenty patients met the inclusion criteria. Median follow-up was 83.5 months. Cervical and intrathoracic anastomoses were performed in 103 and 17 patients, respectively. A higher rate of CT findings was found in postoperative imaging (n = 51 [42.5%] vs. n = 13 [10.8%] respectively, p < 0.05). Most of these were found in the lower lobes (61%). A higher rate of lesions was found among patients in whom the conduit was bulging to the right hemithorax compared with totally mediastinal or completely in the right hemithorax (54.5 vs. 35.2% and 34.6%, respectively, p < 0.05). No correlation was found with conduit diameter or anastomotic site. These lesions were more prevalent among patients who complained of reflux or cough during meals (NS).Conclusions A significantly higher rate of new CT findings was found in postoperative imaging of this post-esophagectomy cohort, suggesting a high incidence of aspirations. The locations of the conduit, rather than anastomosis site, seem to play a role in the development of these findings. Further research is needed to evaluate the clinical significance of these findings.
Keywords: esophagectomy; aspiration; imaging